ADAMTS 13 deficiency is associated with abnormal distribution of von Willebrand factor multimers in patients with COVID-19. Issue 204 (August 2021) - Pascreau, Tiffany; Zia-Chahabi, Sara; Zuber, Benjamin; Tcherakian, Colas; Farfour, Eric; Vasse, Marc
Highlights: The ADAMTS 13 deficiency is quantitative in patients with COVID-19. Our results suggested a mechanism of consumption of the protease by high level of VWF. ADAMTS 13 antigen level has a predictive value for intensive care unit admission. The loss of high molecular weight multimers of VWF contrast with the ADAMTS 13 deficiency.